Cannabis Use and Supply Patterns Among Belgian Cannabis Social Club Members. (October 2018) - Pardal, Mafalda; Decorte, Tom
Cannabis Social Clubs (CSCs) constitute a noncommercial model for the supply of cannabis among registered, adults users, which is present in several countries—including in Belgium. This analysis provides a first descriptive examination of a sample of Belgian CSC members' patterns of use and supply, as well as their sociodemographic features. According to a new voluntary survey of 190 Belgian CSC members, more than three quarters are male, Belgian, and more than half work full- or part-time. About 44% of respondents have completed university studies. Securing cannabis was the primary reason to adhere to a CSC, and most are (near-)daily users. Our results revealed that the CSC was the sole supplier for most respondents of cannabis-producing CSCs, who obtained almost exclusively (dried) herbal cannabis. The presence of (self-declared) medical users in our sample is noteworthy. This analysis advances our knowledge of the segment of the market served by this noncommercial model.